Improvement of Front Roll Learning Outcomes Through the Application of a Cooperative Learning Model With the Help of Audiovisual Media in Students in Grades X-9 of SMAN 1 Banjarbaru - Norliyani, Aulia; Indah, Eka Purnama; Sani, Abdullah (Empiricism Journal, 2026)
This research was conducted based on the low learning outcomes of students in grades X-9 of SMA Negeri 1 Banjarbaru on the front bolster floor gymnastics material. Although cooperative learning models and audiovisual media have been widely applied in Physical Education learning, there is still limited classroom action research that examines the combination of the two in improving the learning outcomes of the front roll through group cooperation activities, peer observation, and structured feedback. This research aims to improve students' front rolling skills through the application of a cooperative learning model assisted by audiovisual media. The research uses the Classroom Action Research (PTK) method which is carried out in two cycles, with each cycle including the stages of planning, implementation of actions, observation, and reflection. The research subjects amounted to 35 students consisting of 12 male students and 23 female students. The research instruments are in the form of observation sheets and learning outcome tests that have been validated by PJOK teachers. The data was analyzed using quantitative descriptive analysis techniques by calculating the percentage of learning completeness and average student scores in each cycle. The results of the study showed that there was an increase in student learning outcomes at each stage of action. In the initial condition, learning completeness reached 26% with an average score of 62. After the implementation of the action in Cycle I, the completeness of learning increased to 57% with an average score of 77. In Cycle II, the completeness of learning increased again to 86% with an average score of 85. Based on the results of the research, it can be concluded that the application of the cooperative learning model assisted by audiovisual media contributes to the improvement of the learning outcomes of students in grades X-9 of SMA Negeri 1 Banjarbaru.